Kekuatan Hukum Berita Acara Penyelesaian Sengketa Tanah Oleh Kelurahan Watolo Sebagai Alas Hak Atas Tanah - Nur Fauzia; Adonia Ivone Laturette; Pieter Radjawane (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Land dispute over the Watolo family was not settled for nearly two decades, on the initiative of one side so that the issue was taken to kelurahan to be settled mediation.Purposes of the Research: To find out the legal force of the minutes of the settlement of land disputes by Watolo Village which is used as the basis for land rights. Methods of the Research: The research method used is the type of normative legal research that is descriptive analytical.Results of the Research: Based on this research, the minutes issued by the kelurahan are not the minutes of the proper meeting and cannot be used as a basis for rights because there are no laws or regulations that guarantee the strength of law and legal certainty and the minutes cannot be used as a basis for internal rights but can be used as evidence by both parties when the land dispute is continued to the trial stage in court.